STRENGTHENING HUMAN RESOURCE MANAGEMENT BASED ON COMPETENCIES AND WORK EXPERIENCE TO IMPROVE EMPLOYEE PERFORMANCE AND RETENTION IN MODERN ORGANISATIONS - Aslan Aslan; Dasa Rahardjo Soesanto (INJOSEDU: International Journal of Social and Education, 2026)
This study examines the strengthening of human resource management based on competencies and work experience to improve employee performance and retention in modern organisations. The aim of this study is to analyse the role of competencies in improving employee performance and the role of work experience in strengthening employee retention. The method used is a literature review with a descriptive-analytical approach, involving a search of various relevant academic sources, such as journals, books and research articles. The findings indicate that competency-based management is capable of improving recruitment accuracy, training effectiveness, the quality of performance appraisals, and career development. On the other hand, work experience plays a crucial role in fostering adaptability, job satisfaction, organisational commitment, and employee loyalty. The integration of these two aspects results in a more effective, adaptive, and organisation-sustainability-oriented HR management system. This study emphasises that modern organisations need to manage competencies and work experience systematically in order to retain high-performing employees and enhance long-term competitiveness.